2021
DOI: 10.1002/smll.202105497
|View full text |Cite
|
Sign up to set email alerts
|

Axial Scanning Metal‐Induced Energy Transfer Microscopy for Extended Range Nanometer‐Sectioning Cell Imaging

Abstract: Nanometer‐sectioning optical microscopy has become an indispensable tool in membrane‐related biomedical studies. Finally, many nanometer‐sectioning imaging schemes, such as variable‐angle total internal reflection fluorescence microscopy, metal‐induced energy transfer (MIET) imaging, and supercritical‐angle fluorescence microscopy have been introduced. However, these methods can measure a single layer of molecules, and the measurement ranges are below 100 nm, which is not large enough to cover the thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In previous studies, MIET has been primarily used for structural analysis, such as mapping the topography of the basal membrane of living cells 31 , reconstructing focal adhesions and stress fibers in three dimensions 34 , measuring the distance between the inner and outer envelope of the nucleus 35 , visualizing the dynamics of epithelial-mesenchymal transitions (EMT) 36 , and enabling single-molecule localization and co-localization along the optical axis 37 , 38 . Additionally, MIET has been utilized to map the basal membrane and lamellipodia of human aortic endothelial cells 39 , 40 and to achieve three-dimensional isotropic resolution imaging of microtubules and clathrin pits in combination with SMLM 41 . By replacing the thin metal film with a single sheet of graphene (Graphene-Induced Energy Transfer or GIET), the localization accuracy can be improved by an order of magnitude within ~25 nm from the substrate 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, MIET has been primarily used for structural analysis, such as mapping the topography of the basal membrane of living cells 31 , reconstructing focal adhesions and stress fibers in three dimensions 34 , measuring the distance between the inner and outer envelope of the nucleus 35 , visualizing the dynamics of epithelial-mesenchymal transitions (EMT) 36 , and enabling single-molecule localization and co-localization along the optical axis 37 , 38 . Additionally, MIET has been utilized to map the basal membrane and lamellipodia of human aortic endothelial cells 39 , 40 and to achieve three-dimensional isotropic resolution imaging of microtubules and clathrin pits in combination with SMLM 41 . By replacing the thin metal film with a single sheet of graphene (Graphene-Induced Energy Transfer or GIET), the localization accuracy can be improved by an order of magnitude within ~25 nm from the substrate 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The localization accuracy depends on the number of detected photons which determines the accuracy of the determined fluorescence lifetime, and with a few thousand of detected photons one typically achieves an axial resolution down to a few nanometers. Previous applications of MIET imaging include mapping the topography of the basal membrane of living cells, 24 threedimensional reconstruction of focal adhesions and stress fibers, 26 measuring the distance between the inner and outer envelope of the nucleus, 27 visualizing the dynamics of epithelial−mesenchymal transitions (EMT), 28 single-molecule localization and colocalization, 29,30 mapping the basal membrane and lamellipodia of human aortic endothelial cells, 31,32 and, in combination with SMLM, three-dimensional isotropic resolution imaging of microtubules and clathrin pits. 33 Recently, it was shown that substituting the metal layer with a single sheet of graphene (graphene-induced energy transfer or GIET imaging) achieves a ca.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, MIET has been primarily used for structural analysis, such as mapping the topography of the basal membrane of living cells [26], reconstructing focal adhesions and stress fibers in three dimensions [29], measuring the distance between the inner and outer envelope of the nucleus [30], visualizing the dynamics of epithelial-mesenchymal transitions (EMT) [31], and enabling single-molecule localization and co-localization along the optical axis [32,33]. Additionally, MIET has been utilized to map the basal membrane and lamellipodia of human aortic endothelial cells [34,35] and to achieve three-dimensional isotropic resolution imaging of microtubules and clathrin pits in combination with SMLM [36]. By replacing the thin metal film with a single sheet of graphene (Graphene-Induced Energy Transfer or GIET), the localization accuracy can be improved by an order of magnitude within ∼25 nm from the substrate [27].…”
Section: Introductionmentioning
confidence: 99%